ANALISIS SISTEM INFORMASI PENJUALAN PUPUK BERBASIS E-COMMERCE: ( STUDI KASUS KECAMATAN SOSA TIMUR ) - Mutmainnah Khairiah Pakpahan; Tartila; Graudi Haekal (CV. Barokah Publsiher, 2022)
Along with the development of the era related to technology and information which is very fast, of course, many factors of life are required to use it. One form of business that is becoming the newest trend at this time is e-commerce. It's the same as the Raro fertilizer shop. To increase their sales they use e-commerce as a form of increasing income and from e-commerce also the public gets information about the Raro fertilizer shop using Facebook, Instagram ,web,shopee and lazada. The approach used in this research is descriptive qualitative. is research conducted to collect information about existing symptoms, meaning to identify symptomatic conditions depending on the circumstances in which the research is carried out. The type of data source used is primary data obtained directly from the data source, in this case the researcher obtained data directly from the workers and shop owners of Raro Fertilizers. Store advertising media is more effective because it applies SEO techniques so that the shop address appears on the main search engine page. Customers do not need to come to the store when ordering fertilizer, because ordering transactions can be done online. By looking at the product list on the website's home page, customers can find out stock and more detailed information about the products being sold.